A Development of DSA Digital Signature Scheme Based on Ring Zn - Le, Van Tuan; Ta, Minh Thanh; Leu, Duc Tan (Old Journal, 2018)
We have known, the DSA scheme is not secure in situations of coinciding or revealing of session key. In this paper, we propose a solution that improves the DSA digital signature scheme on ring Zn. The idea of our solution is developing the DSA scheme, in which its security is based on discrete logarithm problem on ring Zn(DLPn), with the modulo number n is a product of two distinct primes. The proposed scheme is secure from the situations of revealing or coinciding of session key, for this advantage, it can be applied into practice.